Pengaruh Profitabilitas, Likuiditas, Dan Aktivitas Terhadap Struktur Modal (Studi pada Perusahaan Sektor Konsumen (Kode E) Bukan Primer yang Terdaftar pada BEI Tahun 2015-2023) - Ontolay, Chelsea Falensia; As’ari, Hasim (CV. ITTC INDONESIA, 2024)
The use of the economy in Indonesia has driven change, including increased corporate activity in the capital market which is essential to compete for access to financial instruments. Financial statements, especially equity, are a key indicator of company performance. A decrease in equity can affect investor confidence and future company growth. This study aims to analyze the effect of profitability, liquidity, and activity on capital structure in non-primary consumer sector companies listed on the Indonesia Stock Exchange during 2015-2023. The methodology used is multiple linear regression analysis with independent variables of profitability (Return on Equity), liquidity (Current Ratio), and activity (Total Asset Turnover), while the dependent variable is Debt-to-Equity Ratio as an indicator of capital structure. The result shows that profitability and activity have significant effect on capital structure, while liquidity has no significant effect. This conclusion emphasizes the importance of the company's ability to generate profits and manage assets to determine the capital structure.